2011
DOI: 10.1007/s00467-011-1872-3
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in children with CKD: should we treat with statins?

Abstract: Dyslipidemia has been shown to be a risk factor for increased cardiovascular morbidity and mortality in adult patients with chronic kidney disease (CKD) stages 2-4. In patients on dialysis, a paradoxical correlation has been found between low cholesterol values and increased mortality rates. No data exist in children. Treatment with statins has been convincingly shown to both reduce blood lipid levels and mortality rates from cardiovascular disease in adult patients in CKD stages 2-4. There is no strong litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
6
0
3
Order By: Relevance
“…However, the authors also commented on the lack of evidence currently available in the pediatric setting. This conclusion was also reached by Tullus [20], who reviewed the use of statins in chronic kidney disease and concluded that there is currently no evidence for a long-term beneficial effect in children with this condition. Another concern is that a study investigating the reported incidence of rhabdomyolysis in the USA concluded that renal dysfunction was associated with a higher risk of fatal outcomes in adult statin users [21].…”
Section: Discussionmentioning
confidence: 81%
“…However, the authors also commented on the lack of evidence currently available in the pediatric setting. This conclusion was also reached by Tullus [20], who reviewed the use of statins in chronic kidney disease and concluded that there is currently no evidence for a long-term beneficial effect in children with this condition. Another concern is that a study investigating the reported incidence of rhabdomyolysis in the USA concluded that renal dysfunction was associated with a higher risk of fatal outcomes in adult statin users [21].…”
Section: Discussionmentioning
confidence: 81%
“…FDA-approved pediatric labeling for statins was based on results from placebo-controlled trial results showing 30-50 % reductions in baseline LDL-C regardless of the statin used. The short-term safety of statin therapy in children is based on clinical trials conducted for durations of 2 years or less [84]. These trials have reported asymptomatic elevations in liver transaminases in 1-5 % of children treated with a statin that reversed upon discontinuation of statin therapy.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
“…Extrapolation of results from dyslipidemia trials conducted in the general adult population to children with CKD is not appropriate because the majority of these trials, which showed treatment benefits and prompted recommendations for more aggressive lipid reduction in moderate-to high-risk adults, were secondary prevention trials and do not apply to children and adolescents in whom primary prevention is the treatment goal [84]. Traditionally, primary prevention trials in adults have not definitively shown the benefits of dyslipidemia treatment in reducing the risk of both coronary and total mortality.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the different etiology of CKD and pathogenesis of CVD in children with CKD, expert statements do not recommend wide use of statins in children with CKD [115]. Moreover, the recent meta-analyses showed that statins used longer than 1 year increase by 9 % the risk of incident diabetes and intensive treatment increases this risk by additional 12 % [116, 117].…”
Section: Pharmacological Treatment Strategiesmentioning
confidence: 99%